Retrovirus-like particles released from the human breast cancer cell line T47-D display type B- and C-related endogenous retroviral sequences. - Seifarth, W (1995)
The human mammary carcinoma cell line T47-D releases retrovirus-like particles of type B morphology in a steroid-dependent manner (I. Keydar, T. Ohno, R. Nayak, R. Sweet, F. Simoni, F. Weiss, S. Karby, R. Mesa-Tejada, and S. Spiegelman, Proc. Natl. Acad. Sci. USA 81:4188-4192, 1984). Furthermore, reverse transcriptase (RT) activity is found to be associated with particle preparations. Using a set of degenerate primers derived from a conserved region of retroviral pol genes, we repeatedly amplified three different retroviral sequences (MLN, FRD, and FTD) from purified T47-D particles in several RT-PCR experiments. Screening of a human genomic library and Southern blot analysis revealed that these sequences are of endogenous origin. ERV-MLN represents a multicopy family of human endogenous retroviral elements (HERVs) with two closely related copies and up to 20 more distantly related members. In contrast, ERV-FRD and ERV-FTD comprise only one copy and five to seven related elements per haploid human genome. DNA sequence analysis of the proviral pol region of ERV-MLN revealed an uninterrupted stretch of 241 amino acids that shows 65% identity with the RT of the type B-related HERV designated HERV-K10. ERV-FRD and ERV-FTD are defective type C-related HERVs. The pol gene of ERV-FRD displays a nucleotide homology of 54% to the gibbon ape leukemia virus, and the pol gene of ERV-FTD is about 67% homologous to members of the RTVL-I family of HERVs. Our results thus indicate that the retroviral particles released by the breast cancer cell line T47-D are probably generated by complementation of several endogenous proviruses and can package retroviral transcripts of different origins.